Building a Bridge Between Research and Practice: Transforming the Pharmaceutical Industry in the digital Era - Loso Judijanto; Jacky Chin; Apt. Irfan Ahsani (Journal of Pharmacopoeia, 2025)
This study aims to describe the role of digital transformation in bridging research and practice in the pharmaceutical industry, while identifying emerging barriers and opportunities. The method used is qualitative research with a descriptive approach, through in-depth interviews, observations, and documentation studies of pharmaceutical industry stakeholders. The results show that digitalization through the use of artificial intelligence, big data analytics, blockchain, and telepharmacy can accelerate the translation of research findings into industrial practice. However, this transformation still faces obstacles such as limited human resources, high investment costs, and regulations that are not yet fully adaptive. This study emphasizes that collaboration between academia, industry, and regulators, supported by digital technology, is key to building a more efficient, innovative, and evidence-based pharmaceutical industry model in the digital era